The relationship between distributed leadership and organizational citizenship behavior among TVET practitioner in Malaysia / Luqman Mahmud, Shaiful Annuar Khalid and Ahmad Nizan Mat Noor - Mahmud, Luqman; Khalid, Shaiful Annuar; Mat Noor, Nizan (Research Management Institute (RMI), 2022)
Since the Organ's initial introduction in 1983, research on Organizational Citizenship Behaviour (OCB) has grown rapidly. Despite its effectiveness in school performance, the OCB is not given much weight in the school administration. 420 educators from 71 Technical and Vocational Education and Training (TVET) institutions in Peninsular Malaysia, including vocational colleges and technical schools, were included in the study's sample. The Ministry of Education directed the researcher to conduct the survey using an online form due to COVID-19. A two-step hierarchical regression was used to evaluate the study's initial hypothesis. Leadership practice and school culture were significantly related to the prediction of responder altruism among the three principal’s Distributed Leadership (DL). Only school culture impacted teachers’ courtesy among the three principals’ DL. Based on the findings, DL predicts teachers’ OCB in a positive and substantial way.